Airport safety, capacity and investment - Brooker, Peter (Cranfield University, 2005)
The title ‘Airport Safety, Capacity and Investment’ could potentially cover an enormous range of topics and approaches. Techniques used include probabilistic risk analysis, queueing theory, operational research, and cost benefit analysis (CBA). The aim here is both to give an impression of the whole subject and to focus on a few key topics. Surveillance technology plays an important part in delivering safety and capacity, but has to be seen in the larger system picture, particularly when investment is contemplated.
Paper presented at SurTech 2002, The Aviation Surveillance Technologies Conference